Relationship between Learning Interest and Learning Outcomes of Catholic Religious Education Students in Grade III of St.Don Bosco Catholic Elementary School Palangkaraya - Andriyanto, Yustinus Dwi (Journal of Childhood Development, 2024)
Learning interest is a students desire and interest in lessons, accompanied by attention and activeness to master the knowledge and experience with pleasure and satisfaction. Concerning the maximum learning outcomes, one of the factors that influence it is interest. In learning actiIIIties, if students have an interest in learning, they will feel learning is very important, therefore they try to focus their attention on matters related to learning actiIIIties and do it with pleasure without coercion from anyone. This study uses quantitative research. The population in the study were 161 students in grades IIIA to III E Catholic Elementary School St. Don Bosco Palangkaraya. The research sample was 30 students who were determined using simple random sampling technique. Research variables are learning interest and learning outcomes. Data collection techniques was using questionnaires and documentation. Data analysis was performed in inferential statistics using the Pearson product moment correlation formula. The results of the study can be described as follows: The correlation value between learning interest and learning outcomes in grade III SDK Santo Don Bosco Palangkaraya is 0.734. This shows a positive correlation. If the correlation value is interpreted by the interpretation table of the correlation coefficient r, then the value is in the correlation interpretation interval 0.80 - 1,000. Thus, the level of the relationship is very strong. This shows that the relationship between student interest is quite good. The coefficient of determination is 53.88%. This shows that the relationship between learning interest and learning outcomes is determined by learning interest and 46.12 is determined by other factors. The significance value between the independent variable and the dependent variable is 5,719. This shows that the calculated t value is greater than the t table value or 5.719> 1.697. Therefore, it is said to be significant between students' learning interest in the Catholic Religion and character Education subjects and student learning outcomes. In that case, Hypothesis Ha: There is a significant relationship between student interest in Catholic Religious and Character Education (X) with student learning outcomes (Y) which have been received.